PENGGUNAAN TEKNOLOGY ACCAPTED MODEL (TAM) DALAM PEMBELIAN TIKET OLAHRAGA DI GAYAM BOJONEGORO - Harjo Lukito (Media Mahardhika, 2020)
The purpose of this study is to find out the effective factors in making people willing to buy back sports tickets online with an approach to expanding the technology acceptance model. This research is considered to expand its functionality, descriptive survey of its systems, and focused on the Structural Equation Model (SEM). Participants are supporters of Gayam Village Volleyball Team who have purchased tickets online at least once. The review of questionnaire data was conducted using SPSS18 and AMOS20. This finding shows that relative trust has the greatest influence on people's expectations and decisions to buy back sports tickets so they have a positive view of the use of such methods. Even the perceived ease of use is second, which means that because the purchase system seems simpler, the incentive to buy will be increased. Ultimately, the utility assumption of the purchasing system will generate optimistic expectations of the use of technology.